2012
DOI: 10.1111/j.1530-0277.2012.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Marketing Receptivity, Marketing‐Specific Cognitions, and Underage Binge Drinking

Abstract: Background Exposure to alcohol marketing is prevalent and is associated with both initiation and progression of alcohol use in underage youth. The mechanism of influence is not well understood, however. This study tests a model that proposes alcohol-specific cognitions as mediators of the relation between alcohol marketing and problematic drinking among experimental underage drinkers. Methods This paper describes a cross-sectional analysis of 1734 U.S. 15–20 year old underage drinkers, recruited for a nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
101
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 49 publications
8
101
0
1
Order By: Relevance
“…This finding is consistent with the Heuristic Marketing Receptivity Model, which posits that marketing-specific cognitions and attitudes in four domains mediate the association between alcohol advertising and consumption: alcohol expectancies, perceptions of alcohol norms, identifying one-self as a drinker, and brand loyalty (McClure et al, 2013). This result might also be understood as a "mere exposure" effect, by which consumers develop a preference for certain products simply because of their greater familiarity, and is an effect that can occur outside conscious awareness (Bornstein, 1989;Zajonc, 2001).…”
supporting
confidence: 85%
“…This finding is consistent with the Heuristic Marketing Receptivity Model, which posits that marketing-specific cognitions and attitudes in four domains mediate the association between alcohol advertising and consumption: alcohol expectancies, perceptions of alcohol norms, identifying one-self as a drinker, and brand loyalty (McClure et al, 2013). This result might also be understood as a "mere exposure" effect, by which consumers develop a preference for certain products simply because of their greater familiarity, and is an effect that can occur outside conscious awareness (Bornstein, 1989;Zajonc, 2001).…”
supporting
confidence: 85%
“…Este resultado es interesante, ya que permite pensar que son los efectos inmediatos del consumo de alcohol (sabor/apariencia poco atractivos) los que en primer lugar podrían llevar a los jóvenes a dejar de consumirlo. Considerando que estudios sobre el marketing de bebidas con alcohol reconocen que las cogniciones positivas en torno a las bebidas alcohólicas se relacionan con el consumo excesivo episódico en jóvenes (McClure, Stoolmiller, Tanski, Engels, & Sargent, 2013) podría pensarse el efecto opuesto. Es decir, las cogniciones negativas que conllevan disgusto podrían derivar en intervenciones para reducir el consumo, en particular el excesivo episódico, en jóvenes.…”
Section: Discussionunclassified
“…However, they did not draw specific conclusions about the effects of ABM, an important distinction given that several studies have identified that the association between drinking and ABM ownership is stronger than that for other marketing variables. [22][23][24][25] Thus, this review sought to explore the current literature on child and adolescent ownership of ABM and the effects of ABM ownership.…”
Section: Jonesmentioning
confidence: 99%
“…In a cross-sectional survey 25 of 1734 ever-drinkers aged 15 to 20 years (remaining participants from an earlier longitudinal study 63 supplemented by a sample of AfricanAmerican youth), one-third (33%) reported owning ABM and ownership had both a direct association with binge drinking and indirect associations (mediated by drinker identity and having a favorite alcohol brand). The article did not report on drinking initiation or recent drinking.…”
mentioning
confidence: 99%
See 1 more Smart Citation